The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.31234/osf.io/g69ha
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A practical guide to doing behavioural research on fake news and misinformation

Abstract: Coincident with the global rise in concern about the spread of misinformation on social media, there has been influx of behavioural research on so-called “fake news” (fabricated or false news headlines that are presented as if legitimate) and other forms of misinformation. These studies often present participants with news content that varies on relevant dimensions (e.g., true v. false, politically consistent v. inconsistent, etc.) and ask participants to make judgments (e.g., accuracy) or choices (e.g., wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In each study, only participants who indicated that they use social media were allowed to participants. Participants were presented one at a time (but in a random order) a set of actual true and false news headlines taken from social media (in the format of a Facebook post; see Pennycook, Binnendyk, et al (2020) for a detailed explanation of the methodology behind headline selection). All of the false headlines were found using popular fact-checking sites such as snopes.com and factcheck.org and all of the true headlines came from reputable mainstream news sources.…”
Section: Experimental Designsmentioning
confidence: 99%
“…In each study, only participants who indicated that they use social media were allowed to participants. Participants were presented one at a time (but in a random order) a set of actual true and false news headlines taken from social media (in the format of a Facebook post; see Pennycook, Binnendyk, et al (2020) for a detailed explanation of the methodology behind headline selection). All of the false headlines were found using popular fact-checking sites such as snopes.com and factcheck.org and all of the true headlines came from reputable mainstream news sources.…”
Section: Experimental Designsmentioning
confidence: 99%
“…Following classic (Clark & Watson, 1995;Loevinger, 1957) and recent (Boateng et al, 2018;Rosellini & Brown, 2021;Zickar, 2020) psychometrics guidelines, and taking into account insights from misinformation scholars (Pennycook, Binnendyk, et al, 2020;Roozenbeek, Maertens, et al, 2021), we devised a four-stage scale development protocol (i.e., 1-item generation, 2-expert filtering, 3-quality control, and 4-data-driven selection), shown in Figure 1.…”
Section: Propertiesmentioning
confidence: 99%
“…There is a debate in the literature on whether the misinformation items administered in misinformation studies should be actual news items circulating in society, or news items created by experts that are fictional but feature common misinformation techniques. The former approach arguably provides better ecological validity (Pennycook, Binnendyk, et al, 2020), while the latter provides a cleaner and less confounded measure since it is less influenced by memory and identity effects (van der Linden & . Considering these two approaches and reflecting on representative stimulus sampling (Dhami et al, 2004), we opted for a novel approach that combines the best of both worlds.…”
Section: Preparatory Stepsmentioning
confidence: 99%
“…Uncorrected contrasts also suggested that such increase was significantly stronger the validity of the content which they were seeing, which could in turn influence any subsequent sharing intention [30,32,75].…”
Section: Supporting Informationmentioning
confidence: 99%